Effect Of Transformational Leadership, Work Environment And Job Satisfaction On Work Discipline At The Transportation Office Of Pasaman Barat District - Fira Yulia; Okki Trinanda (Human Resource Management Studies, 2022)
This study aims to prove and analyze the effect of transformational leadership, work environment and job satisfaction on the work discipline of the employees of the West Pasaman Regency Transportation Service. In this study, several employees of the West Pasaman Regency Transportation Service were used randomly. The analytical method used to prove the truth of the hypothesis is multiple regression and t-statistical testing. The data processing is done by using SPSS. The results of data processing that has been done found that transformational leadership has an effect on discipline, at the stage of testing the second and third hypotheses it was found that the work environment has an effect on employee work discipline while job satisfaction also has a significant effect on job satisfaction of the employees of the Department of Transportation, West Pasaman Regency.